Circular RNA profiling identifies circ_0001522, circ_0001278, and circ_0001801 as predictors of unfavorable prognosis and drivers of triple-negative breast cancer hallmarks - Dania Awata; Vishnubalaji Radhakrishnan; Hibah Shaath; Ramesh Elango; Sameera Rashid; Mohammed Akhtar; Thasni Karedath Abdul Azis; Ikhlak Ahmed; Khalid Ouararhni; Ammira S. Al-Shabeeb Akil; Nehad M. Alajez (Cell Death Discovery)
Abstract Breast cancer poses a significant clinical challenge due to its complex molecular landscape, underscoring the need for improved prognostic and therapeutic strategies. In this study, we explored the expression profiles and therapeutic relevance of circular RNAs (circRNAs) in a cohort of 96 breast cancer patients from Qatar representing the MENA region. Our data identified distinct expression patterns in relation to breast cancer subtypes, tumor grade, and age, with fifty circRNAs found to be associated with unfavorable relapse-free survival (RFS). The expression of sixteen of these circRNAs was validated in triple-negative breast cancer (TNBC) model using RNase R resistance assay. Among these, the expression of circ_0001522, circ_0001278, and circ_0001801 was validated using divergent primers, and their backsplice junctions were confirmed using Sanger sequencing. Functionally, siRNA-mediated knockdown of these circRNAs significantly suppressed cell proliferation, colony formation, three-dimensional organoid growth, and cell migration in TNBC models. Mechanistic investigations revealed that circRNA depletion altered a subset of miRNA and mRNA expressions, with key interactions involving miR-4458, miR-145-5p, and miR-760, regulating critical targets such as CCND1, ROBO4, and MMP1. Additionally, circRNA-RBP bioinformatic analysis identified common binding partners, including AGO2, CPSF7, TARDBP, UPF1, and LIN28B, suggesting roles in post-transcriptional regulation. Our data highlight circ_0001522, circ_0001278, and circ_0001801 as promising prognostic and therapeutic circRNA targets for breast cancer, offering new avenues for improving breast cancer prognosis and treatment.